Invariant attribute computation and characterisation of surface texture - Roop Kishor Goyal. (2009)
Texture is an important property for identification of objects in a scene. Texture analysis techniques can be broadly classified into two categories, namely statistical and structural techniques. Statistical techniques consider an image as a random field and compute local features of image. Structural techniques characterise a texture image on the basis of the texture element attributes and their placement.